Pengaruh Pemberian Terapi Latihan Pelvic Tilt Terhadap Penurunan Nyeri pada Pasien Low Back Pain ec. Hernia Nucleus Pulposus di Rumah Sakit Elizabeth Situbondo - Mizan Abdul Rouuf; Agung Hadi Endaryanto; Dian Pitaloka Priasmoro; Ahmad Abdullah (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: Low back pain is a condition when the back is so painful that it interferes with daily activities. One way to reduce pain is by using pelvic tilting physiotherapy exercises. This study aims to identify the pain scale in low back pain patients before and after pelvic tilting exercise, and to analyze the effect of pelvic tilting exercise therapy on reducing pain in patients with low back pain ec hernia nucleus pulposus.Methods:  The independent variable in this study was a pelvic tilting exercise suit, the dependent variable was pain reduction. This study has 15 respondents using purposive sampling. . The design of this study used a one group pretest and posttest design.Results:  The results of this study are p-value = 0.000 (p <0.05) meaning that there is  effect of giving pelvic tilting exercise therapy to reduce pain in low back pain patients. ec Hernia Nucleus Pulposus at Elizabeth Situbondo Hospital in 2021Conclusion: 1.  the average pain scale pain scale before giving pelvic tilting exercise therapy is 6.20, which is moderate pain.2.  the average pain scale after giving pelvic tilting exercise therapy is 3.26,, namely mild pain.3. There is an  effect of giving pelvic tilting exercise therapy to reduce pain in low back pain patients. ec Hernia Nucleus Pulposus at Elizabeth Situbondo Hospital with p-value = 0.000 (p<0.05)